Anticholinergic Drugs Interact With Neuroprotective Chaperone L-PGDS and Modulate Cytotoxicity of Aβ Amyloids - Low, Kimberly Jia Yi; Phillips, Margaret; Pervushin, Konstantin (Frontiers in Pharmacology, 2020)
Anticholinergic drugs can be used as a treatment for many diseases. However, anticholinergic drugs are also known for their cognition-related side effects. Recently, there has been an increasing number of reports indicating a positive association between exposure to anticholinergic drugs and the Alzheimer’s disease (AD). Our novel study provides evidence of interactions between two representative anticholinergic drugs [Chlorpheniramine (CPM), a common antihistamine, and Trazodone (TRD), an antidepressant] with neuroprotective amyloid-beta (A) chaperone, lipocalin-type prostaglandin D synthase (L-PGDS) and the amyloid beta-peptide (1-40). Here, we demonstrate that -CPM and TRD -bind to L-PGDS with high affinity where chlorpheniramine exhibited higher inhibitory effects on L-PGDS as compared to Trazodone. We also show that the interactions between the drug molecules and A(1-40) peptides result in an higher fibrillar content of A(1-40) fibrils with altered fibril morphology. These altered fibrils possess higher cytotoxicity compared to Aβ(1-40) fibrils formed in the absence of the drugs. Overall, our data suggest a mechanistic link between exposure to anticholinergic drugs and increased risk of Alzheimer’s disease via inhibition of the neuroprotective chaperone L-PGDS and direct modification of Aamyloid morphology and cytotoxicity.